Isotopic composition of rainwater nitrate at Bermuda: The influence of air mass source and chemistry in the marine boundary layer. Issue 19 (2nd October 2013) - Altieri, K. E.; Hastings, M. G.; Gobel, A. R.; Peters, A. J.; Sigman, D. M.
Abstract [1] Emissions of anthropogenic nitrogen (N) to the atmosphere have increased tenfold since preindustrial times, resulting in increased N deposition to terrestrial and coastal ecosystems. The current sources of N deposition to the ocean, however, are poorly understood. To investigate the sources of nitrate in rainwater deposited to the ocean, two years of daily rainwater samples were collected on the island of Bermuda in the western North Atlantic. Air mass back trajectories were computed for each sample and two dominant regimes were identified: slow moving events that originate over the ocean and occur all year, and fast moving events that originate over the continental USA and occur primarily during the cool season (October–March). Marine‐influenced air masses result in rainwater nitrate with lower concentrations, higher average δ15N, and lower average δ18O (4.4 μM, −1.1‰ versus N2 in air, and 69.0‰ versus Vienna SMOW, respectively) than those influenced by North American air masses (6.3 μM, −5.4‰, and 75.0‰). The δ15N decrease and concentration increase from marine to continental air masses are due to a change in NOx source, with increased anthropogenic inputs associated with continental air. We suggest that heterogeneous halogen chemistry in the marine boundary layer leads to isotopic fractionation. This causes higher δ15N‐NO3− to be deposited near the coast and lower δ15N‐NOx to be transported over the open ocean, yielding a low δ15N for anthropogenic NO3− deposition. It is possible that this process also contributes to variations in δ15N‐NO3− from marine air masses. There is a negative linear correlation (r2 = 0.58) between δ15N and δ18O which is driven by the seasonal change in trajectory influencing both the source NOx and the nitrate formation pathways.